Encyclopedia of recreation and leisure in America / Gary S. Cross, editor in chief. - Cross, Gary S. (Scribner American civilization series., 2004)
"This set offers a fascinating look at how Americans spend their free time and entertain themselves. A total of 271 essays present chiefly historical perspectives in the fields of American and cultural studies, sociology, recreation, sports, and leisure studies. Entries cover all facets of American leisure with topics ranging from auctions and blood sports to shopping malls and theme parks. Articles range in length between two and six pages and include brief bibliographies."--"Reference that rocks," American Libraries, May 2005.